The Rate of Gestational Weight Gain are Associated with Preterm Birth in Pregnant Women at Low Risk for Preterm Birth: A Single-Center, Observational Study - Quanfeng Wu; Huanxi Li; Wei Wei; Xueyan Lin; Weiwei Yu; Xueqin Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: Preterm birth (PTB) is the main cause of infant disease and death worldwide. Approximately 70% of neonatal deaths and 36% of infant deaths worldwide are caused by premature birth. Gestational weight gain (GWG) is associated with adverse pregnancy outcomes. This study explored the relationship between the rate of GWG and PTB among pregnant women at low risk of preterm birth. Methods: Our study used a cohort of mother-child pairs with a one-and-a-half-year follow-up from January 2020 to June 2021. We excluded pregnant women with undisputed high-risk factors for PTB and the remaining women were considered the low-risk group. The average rate of GWG was utilized in this research as the measure of GWG. Multivariate logistic regression was used to evaluate the relationship between GWG and PTB among pregnant women at low risk for preterm birth. Results: The final cohort study of mother-child pairs included 3480 pregnant women in the low-risk group. Women with low GWG had a higher possibility of PTB than those with adequate GWG. Comparing underweight women with an adequate GWG rate to underweight women with a low GWG rate, PTB risk increased by 2.52-fold with a low GWG rate. Compared to women with adequate GWG, underweight women with excessive GWG had significantly higher odds of PTB. No significant results were observed for pregnant women classified as overweight or obese. Conclusions: A reasonable GWG during pregnancy can effectively reduce the risk of PTB, especially for pregnant women with low pre-pregnancy body mass index. Low or excessive GWG may lead to an increased risk of PTB.